ASSESSING STUDENTS' MATHEMATICAL PROBLEM-SOLVING ABILITY - Sufyani Prabawanto; Nadya Syifa Utami; Aneu Pebrianti (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Students' ability to solve mathematical problems is the most important part of learning mathematics. Therefore, assessing students' ability to solve mathematical problems is one of the tasks of mathematics teachers that must be done. This study aims to develop a test instrument to assess students' ability to solve mathematical problems. The research method used Systematic Literature Review (SLR) by analyzing primary sources from books and articles. Before developing an instrument to assess students' ability to solve mathematical problems, the variables involved in mathematical problem solving were first analyzed. Furthermore, there are four domains involved in the instrument development framework carried out. They are resources, heuristics, control, and belief system. Based on this study, it was found that: (1) the aspects correlated with mathematical problem solving are reasoning, decision making, critical thinking, and creative thinking; (2) the types of tasks related to mathematical problem solving can be viewed from the structure, the number of essential steps needed to reach the solution, its orientation, and its presentation.